Human Capital in the 21st Century - Kim, Jim Yong (2016)
Jim Yong Kim, President of the World Bank Group, discusses the Ebola epidemic as continuing as a serious threat, not only in terms of human lives, especially in the three most affected countries - Guinea, Liberia, and Sierra, but to the regional and global economies as well. He then addressed educational reform. To promote inclusive growth, the World Bank Group works to facilitate the diffusion of knowledge and support countries in investing in the productivity and skills of their people. Taking on new challenges, solving problems creatively, and working across different backgrounds and cultures, will be important tasks for the vast majority of human beings in the 21st century. He discussed shortcomings of Korea’s educational system.